Mechanics of Biological Systems & Micro-and Nanomechanics, Volume 4 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Grady, Martha; Minary, Majid; Starman, La Vern; Hay, Jenny; Notbohm, Jacob (Conference Proceedings of the Society for Experimental Mechanics Series, 2019)
Mechanics of Biological Systems & Micro-and Nanomechanics, Volume 4 of the Proceedings of the 2018 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fourth volume of eight from the Conference, brings together contributions to important areas of research and engineering. The collection presents early findings and case studies on a wide range of topics, including: Cell Mechanics & Traumatic Brain Injury Micromechanical Testing Adhesion and Fracture MEMS Devices and Technology Nano-scale Deformation Mechanisms 1D & 2D Materials Tribology & Wear Research and Applications in Progress.